Risk of multiple myeloma in a case–spouse study. Issue 6 (2nd June 2016) - Andreotti, Gabriella; Katz, Michael; Hoering, Antje; Van Ness, Brian; Crowley, John; Morgan, Gareth; Hoover, Robert N.; Baris, Dalsu; Durie, Brian
Abstract: This study examined lifestyle, occupation, medical history and medication use with multiple myeloma risk in a case–spouse study (481 patients, 351 spouses). Odds ratios (ORs) and 95% confidence intervals (CI) were calculated using logistic regression. Compared to spouse controls, cases were more likely to have a family history of multiple myeloma (OR = 2.8, 95% CI = 1.2–6.4) and smoked cigarettes (OR = 1.7, 95% CI = 1.2–2.5), but less likely to have consumed alcohol (OR = 0.6, 95% CI = 0.4–0.9). Nurse/health practitioners (OR = 2.8, 95% CI = 1.3–6.2) and production workers (OR = 3.7, 95% CI = 1.0–13.7) had significantly increased risks; and some occupations linked to diesel exhaust had elevated, but non-significant, risks. History of herpes simplex (OR = 1.7, 95% CI = 1.2–2.4), shingles (OR = 1.7, 95% CI = 1.1–2.7), sexually transmitted diseases (OR = 2.0, 95% CI = 1.0–3.7) and medication allergies (OR = 1.7, 95% CI = 1.2–2.4) were associated with higher risks. Use of angiotensin-converting enzyme inhibitors, anti-convulsants, antidepressants, statins and diuretics were associated with reduced risks. The results are consistent with previous population-based studies and support the utility of patient databanks and spouse controls as a resource in epidemiologic research.